Emotion detecting humanoid – the use of GPSO Algorithm - Bashir, Mohammed Ghandi; Ramachandran, Nagarajan, Prof. Dr.; Hazry, Desa, Assoc. Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.